An Experiential Approach to Mentoring Academic Leaders: Review, Practice, Report - Julie A. Ray; Victor R. Wilburn; Melissa Odegard-Koester; Jeremy Ball (Academic Chairpersons Conference Proceedings, 2018)
This session presents a leadership development program where new department chairs discuss best practices and realistic challenges with seasoned chairs, helping all to improve their leadership skills through a supportive group process. The program includes a summer book study, monthly meetings, a department chair handbook, and leadership resources.
Keywords: Leadership; Mentoring; Department Chairs; Development; Resources